Loneliness in Millenial Generation - Kustanti, Aditya Febriani; Anwar, Anwar; Rahmatulloh, Ainurizan Ridho (Universitas Mercu Buana Yogyakarta, 2022)
Loneliness is a condition where there is a difference between the relationship that an individual has with the relationship that the individual expects, both in the quality and quantity. This study aimed to determine the overview of loneliness in the Indonesian millennial generation. Research on loneliness is important due to the large impact and the large population of millennials in Indonesia.This study was conducted on 168 individuals who belong to the millennial generation. Millennials are individual who born in the period of 1982-1999. The research method used is questionnaire research, where the questionnaires are distributed online. The questionnaire used is a loneliness scale which was compiled by the researcher himself with reference to Weiss (1972) theory. The approach used in this study is quantitative, and the analysis used is descriptive analysis. The results of this study showed that the level of loneliness in millennial generation was in the moderate category, the type of loneliness in the unclassified category. This study also shows that gender provide a more diverse overview of the level and type of loneliness in millennials.